Exploring the Role of Non-Formal Education in Tourism Resource Management - A. Vinodan; S. Meera (Australian Journal of Environmental Education)
This study investigates the pivotal role of non-formal education in enhancing ecotourism resource management, aiming to elevate contemporary practices in the field. Utilizing a comprehensive methodology involving focus group discussions and expert interviews held at Parambikulam and Periyar Tiger Reserves of Kerala, India, the research employs latent content analysis to extract critical elements. The identified components of non-formal education programmes—education, awareness and interpretations—underscore their multifaceted nature within (eco)tourism destinations. Beyond unveiling strategies, the study scrutinises gaps in community interventions and their alignment with global mandates like the post-Aichi Target and Sustainable Development Goals (SDGs). Urging immediate action from policymakers, administrators and stakeholders, the research advocates for incentive-based mechanisms aligning with post-Aichi Target and SDG objectives. The study emphasises community-based non-formal education programmes foster community involvement and encourages social and cultural interventions. Significantly, these programmes contribute to biodiversity conservation by disseminating locally generated, authentic information. This research underscores the transformative potential of incentivized, community-driven, non-formal education, emphasising its crucial role in advancing local communities and global sustainability goals.